FACTORS THAT AFFECT DENGUE PREVENTION EFFORTS IN THE WORKING AREA OF THE PEUSANGAN KEC HEALTH CENTER. BIREUEN ACEH REGENCY - Nasution, Ramadhani Syafitri; Theo, Deli; Safitri, Sari (HEARTY, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease transmitted through the bite of the Aedes aegypti mosquito and is still a public health problem. Dengue cases in the work area of the Peusangan Health Center continue to increase every year, so it becomes a threat to family health. This study aims to find out the factors that affect dengue prevention efforts in the working area of the Peusangan Health Center, Peusangan District, Bireuen Regency. The study uses a quantitative design with an analytical survey through a cross sectional study approach. The population is the entire community in nine villages with a total of 19,271 families. The sample was determined by stratified random sampling of 99 families. Data analysis was carried out in univariate, bivariate, and multivariate manners. The results of the study show that education, knowledge, attitudes, the role of health workers, water reservoirs, and the existence of waste have an effect on dengue prevention efforts. The most dominant factor was education with a value of p = 0.000 < 0.025; CI 95% = 5,389–316,539; and OR = 41.154. It was concluded that the educational variable has an important role in the prevention of dengue. The Peusangan Health Center is advised to conduct regular larval checks every three months, carry out fogging, and improve health promotion through the application of the 3M Plus principle to reduce the incidence of dengue incidence.